Little Architects, Big Ideas: Climate Action Through Design-Based Learning - Türeli, Ipek; Malhamé, Nathalie; Nabi, Sarah (The Canadian Journal of Action Research)

(untitled) (Canadian Association of Action Research in Education, 2025)
This study explores how architecture can support climate change education and examines how children develop climate action concepts through design. In response to increased eco-anxiety among children due to climate change, the research explores how and if architecture can empower students as future designers. The study was conducted as a five-week action research project in collaboration with a local public school and the participation of two fourth grade classes. The study involved children participating in an architecture program adjusted to their existing ministry-approved curriculum, and enriched by two exhibitions, one at their school for their school community and families and another one at a university. Findings highlight the versatility of architecture as a cross-curricular subject and the importance of using design education to foster empathy, agency, and a sense of responsibility in addressing climate change.